Status of Import of Wood in Punjab : do we Really Need that ? - Bisht, N. S.; Singh, C. J. (Indian Forester, 2007)
Punjab is predominantly an agriculture state having over 85 per cent of its land area under agriculture crops. Large quantity of wood is being imported from abroad to meet the demand of construction sector, furniture units, truck body building units and sports goods industries. It has reduced the use of indigenous species considerably in these sectors. Of late, poplar and Eucalyptus plantations have been adopted by the farmers in a big way due to their large-scale use in plywood and veneer industries. At present the state is able to meet around sixty per cent of its annual demand of industrial wood from local production. The situation can be improved by providing certain incentives to the tree growers such as, financial loans at low interest rates, market support and even subsidies.